Knowledge and Perspectives of Postgraduate Nurses regarding Competency of Advanced Nursing Practice in Kurdistan Region of Iraq - Bootan Hasan Ahmed; Ribwar Arsalan Mohammed; Sanaa Hassan Abdulsahib; Vian Afan Naqshbandi (Hawler Medical University, 2018)
Background and objectives: Advanced nursing practice (ANP) involves integration role domains, which are related to clinical practice, education, research, professional development and organizational leadership. The objectives of this study were to assess the knowledge and perspective of graduated nurse regarding competency of advanced nursing practice and explain the domains of advanced nursing practice competency. Methods: This cross-sectional study sought to determine knowledge and perspective of graduated nurses regarding advanced nursing practice in Kurdistan region from 20th June 2014 to 20th December 2014. Nurses who held degrees including Master of Science, and Philosophy of Doctorate or both were invited to participate. One hundred and fifty participants met the inclusion criteria, and 50 completely responded to the questionnaire. Data were analyzed by using Statistical Package for the Social Sciences (SPSS) Version (20). Results: The total 50 of interviewed participants responded to the survey, with 24 (48%) considering that an ANP should have autonomy in clinical practice. While 28 (56 %) and 35 (70 %) of participants mentioned that an ANP should be able to manage complexity throughout clinical placement. Conclusion: Considerable number of participants in this study did not have adequate and satisfactory knowledge regarding advanced nursing practice.